Air pollution tolerance index of selected tree species in urbanized areas of Butuan City, Philippines - Amor M. Natividad; Reymond C. Sandueta; Chime Mora-Garcia (Annals of Tropical Research)
Assessing the sensitivity or tolerance of plants to air pollution is a valuable method to address the issue of air pollution in a locality. The aim of this study was to examine the Air Pollution Tolerance Index (APTI) of selected tree species in significant locations in Butuan City. This study purposively sampled 19 tree species collected from three areas in Butuan City. The trees were evaluated using APTI which consists of four parameters: leaf-extract pH, relative water content, total chlorophyll content, and ascorbic acid content. The selected tree species were categorized as tolerant, intermediately tolerant, and sensitive based on the calculated APTI. The APTI results revealed that only three species namely Ficus elastica, Premna odorata, and Mangifera altissima were identified to be tolerant species and could be suitable to act as sinks of air pollutants. Sensitive species were Inocarpus fagifer and Terminalia catappa. APTI can be a useful tool that can help plan and decided which tree species to plant in greenbelt areas in the city to remediate air pollutants.